The regulatory function of LexA is temperature-dependent in the deep-sea bacterium Shewanella piezotolerans WP3 - Jian, Huahua; Xiong, Lei; He, Ying; Xiao, Xiang (Frontiers in Microbiology, 2015)
The SOS response addresses DNA lesions and is conserved in the bacterial domain. The response is governed by the DNA binding protein LexA, which has been characterized in model microorganisms such as Escherichia coli. However, our understandings of its roles in deep-sea bacteria are limited. Here, the influence of LexA on the phenotype and gene transcription of Shewanella piezotolerans WP3 (WP3) was investigated by constructing a lexA deletion strain (WP3ΔlexA), which was compared with the wild-type strain. No growth defect was observed for WP3ΔlexA. A total of 481 and 108 genes were differentially expressed at 20°C and 4°C, respectively, as demonstrated by comparative whole genome microarray analysis. Furthermore, the swarming motility and DMSO reduction assay demonstrated that the function of LexA was related to temperature. The transcription of the lexA gene was up-regulated during cold acclimatization and after cold shock, indicating that the higher expression level of LexA at low temperatures may be responsible for its temperature-dependent functions. The deep-sea microorganism Shewanella piezotolerans WP3 is the only bacterial species whose SOS regulator has been demonstrated to be significantly influenced by environmental temperatures to date. Our data support the hypothesis that SOS is a formidable strategy used by bacteria against various environmental stresses.